“Childless cat ladies” and the 2024 US presidential election - Lori R. Kogan; Shelby E. McDonald; Laura E.T. Swan (Human-Animal Interactions, 2024)
Abstract Introduction: This study, part of a larger research project assessing the political views of people with pets (dogs and cats), investigates the political views and life satisfaction of women without children who own cats. The research aims to provide insights into this group’s perspectives on current issues, including abortion rights and voting intentions for the 2024 US presidential election. Methods: A cross-sectional online survey was conducted in August 2024, involving 236 American women cat owners without children, recruited through Prolific, an online marketplace for survey respondents. The survey assessed the sample’s demographics, life satisfaction using the Satisfaction with Life Scale (SWLS), concerns about current events, views on abortion, political affiliation, and voting intentions. Results: Participants mean SWLS score was 18.64 (SD = 7.74), comparable to other adult populations. The majority identified as liberal (71%) and Democrat (54%). This population’s top concerns included healthcare, abortion rights, climate change and environment, and government ethics. A total of 88.1% believed abortion should be legal in all or most circumstances. Regarding the 2024 election, 86.4% plan to vote, with 72.9% of those planning to vote indicating they support the Harris/Walz ticket. Discussion/Conclusion: The findings suggest that childless women with cats are a politically engaged population with predominantly liberal views. While study limitations include lack of racial and ethnic diversity in the sample, this research provides valuable insights into the political leanings and life satisfaction of an often-stereotyped group.